Diversion in Handling Non-Criminal Offences Committed by Children (Sociology of Law Study) - Kurniawan (Zabags International Journal of Engagement, 2025)
Many children commit crimes and their resolution is through diversion. Diversion is an action or treatment to divert a case from a formal process to an informal process or to remove a child criminal from the juvenile justice system or to remove a child criminal from the criminal justice system. The research method used in this study is normative legal research, by examining legal aspects through statutory regulations as the main legal material by examining theories, concepts, and legal principles related to the legal issues related to this research, so that a legal analysis can be compiled. The results of the study obtained the Implementation of Diversion in the Juvenile Criminal Justice System to Realize Restorative Justice, Reviewed from the Perspective of Legal Sociology, based on the explanation of Article 2 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, each of the principles above includes: Protection, Justice, Non-discrimination, Best interests for children, Respect for children's opinions, Survival and development of children, Guidance is an activity to improve the quality of piety to God Almighty, Proportionality and Deprivation is the last resort.